1959
DOI: 10.1039/tf9595501924
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of oxygen and hot gold. Part 1

Abstract: The behaviour of hot gold filaments, in vacuum and in oxygen at pressures of a few microns of mercury, has been studied. Two main effects were observed-the disappearance of gaseous oxygen and a rate of evaporation of gold considerably greater in oxygen than in vacuum.The rate of disappearance of oxygen ( E ) depended on the purity of the gold, but the amount which disappeared was too large to be explained as oxidation of impurities in the metal. The disappearance is attributed to an impurity-catalyzed conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1961
1961
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Both the quantity of oxygen taken up and the rate of adsorption increased with increasing temperature. Recently, Carpenter, Clark,Main,and Dickson,4 studying changes of the pressure of oxygen in contact with 883°g old surfaces of variable purity, concluded that metallic impurities in the gold are oxidized, suggesting that gold surfaces are contaminated by surface films of metallic impurities from the gold. Shishakov,6 from electron diffraction studies at room temperature, concluded that gold heated at 500°in oxygen at atmospheric pressure is coated with gold peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Both the quantity of oxygen taken up and the rate of adsorption increased with increasing temperature. Recently, Carpenter, Clark,Main,and Dickson,4 studying changes of the pressure of oxygen in contact with 883°g old surfaces of variable purity, concluded that metallic impurities in the gold are oxidized, suggesting that gold surfaces are contaminated by surface films of metallic impurities from the gold. Shishakov,6 from electron diffraction studies at room temperature, concluded that gold heated at 500°in oxygen at atmospheric pressure is coated with gold peroxide.…”
Section: Introductionmentioning
confidence: 99%